Connecting spiritual others: Gandhi and Tutu's discourses on establishing pre-dialogue foundations for interfaith encounters - Jonas, Kyle Michael, author; Aoki, Eric, advisor; Burgchardt, Carl, committee member; Cowell, Pattie, committee member (Colorado State University. Libraries, 2011)
This thesis seeks to understand how spiritual leaders' rhetoric can work towards promoting pre-dialogue foundations for encountering spiritual others. The three research questions that guide my analysis are: first, how does the discourse of two influential spiritual leaders (i.e., Mahatma Gandhi and Desmond Tutu) provide pluralistic insight for understanding spiritual others in an interfaith context? Second, what are common themes/philosophies between these two spiritual leaders, and how do these themes provide a foundation for preparing individuals to enter interfaith dialogue with a pluralistic mindset? And third, how do relational dialectics, humility, and identification in the leaders' discourses lead to a better understanding of how spaces for interfaith dialogue are potentially opened up? In my analysis, I find that Gandhi and Tutu both define religion in a unique way that encourages interfaith dialogue. Both leaders call for humility and embody it throughout their discourse in a way that promotes self-awareness, openness, and transcendence among individuals. Dialogue's primary tension, totality, and the same/different contradiction are dialectical themes addressed by both spiritual leaders. Both leaders instill pluralistic attitudes that help individuals manage their primary tensions, reflect on their relation to spiritual others through totality, and recognize the similarities and differences between faiths. Finally, identification is prevalent throughout both leaders' discourses to reveal the theme of commonality among faiths. This thesis analyzes how Gandhi and Tutu's discourses potentially function to unite spiritual others towards goals of peaceful interfaith coexistence.
Keywords: Gandhi; Tutu; religion; interfaith